Basic assumptions underlying conditioning exercise programs for age-group athletes - Rushall, B. S.; Marsden, J. (1997)
The design of this program is influenced by several principles of growth and development. It is believed that these principles should be adhered to because they are in the best interests of age-group swimmers. The design assumptions are listed.